A micromechanical model for the elastic–plastic behavior of porous rocks. (October 2015) - Zeng, T.; Shao, J.F.; Xu, W.Y.
Abstract: In this paper, we propose a polycrystalline model to study the elastic–plastic behavior of porous rocks. The proposed model will be applied to sandstone. For this purpose, the microstructure of porous rocks will be represented by an assembly of discrete grains and pores. The plastic deformation of each grain is related to the frictional sliding along a number of weakness planes. A specific plastic model is devised to describe the sliding phenomena to take into account the characteristics of rocks such as the pressure dependency and the volumetric dilatancy. A homogenization approach–self-consistent is developed to account for the interactions between grains and pores. An efficient numerical procedure for model implementation is proposed. Finally, we present a series of numerical investigations and comparisons with experimental data to assess the capability of the proposed model to capture the main features of mechanical behaviors of porous rocks.